Analysis of Savings and Loans Scheme by Family Welfare Empowerment Organization As a Fulfillment Solution for Muslim in the Pandemic Outbreak - Helti Nur Aisyiah; Alvin Yahya (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
This study aims to analyze the savings and loans scheme at the Family Welfare Empowerment Organization (FWEO) at the Neighborhood Association (NA) XY, Karanganyar Regency, during the Covid-19 pandemic outbreak. This study uses a qualitative approach with the method of observation and interviews. Observations observe the object of research when transacting savings and loans and the distribution of residual income. Interviews confirmed people who are directly related to the savings and loans activities at FWEO of NA XY including the chairperson, fund administrator of FWEO and Muslim borrowers.The results of the study show that the savings and loans activities at FWEO of NA XY are family-based community activities and prioritize the principle of ta'awun or mutual assistance. One of the assistance is given to Muslims members of FWEO and suffering from financial difficulties during the pandemic outbreak. The principle of ta'awun is reflected by the scheme of savings, loans and the ease use of residual income and based on trust among members. This fact supports the findings that the existence of FWEO in NA XY makes it easier for Muslims to obtain funds as well as to ease the economic burden, especially for those affected by Covid-19.